Prediction of bearing capacity of shallow sites by seismic method - Ramli, Ahmad Bukhari; Kasa, Anuar; Abd. Rahman, Norinah; Mohd Nayan, Khairul Anuar (Taylor's University, 2020)
This paper presents a study of estimating bearing capacity of shallow sites using an alternatives method, which is nondestructive in nature without performing any borehole. Initially, two important parameters, which are, shear wave velocity profile and damping collected by means of Spectral Analysis of Surface Waves method. Shear waves velocity used to provide an elastic Shear Modulus G, and Young’s Modulus, E. Damping at current strain is obtained by using Halfpower Bandwidth Method with various sources from possible low to high frequency. Both parameters, which is measured at low strain, used to adjust to larger strains through hyperbolic relationships with reference strains obtained from the equation. Comparison to conventional method Plate Load Tests and an empirical equation provided previous researcher were made and good agreement achieved by different of 10%.